Case Report: A child with NFKB1 haploinsufficiency explaining the linkage between immunodeficiency and short stature - Ricci, S.; Abu-Rumeileh, S.; Campagna, N.; Barbati, F.; Stagi, S.; Canessa, C.; Lodi, L.; Palterer, B.; Maggi, L.; Matucci, A.; Vultaggio, A.; Annunziato, F.; et al. (Frontiers in Immunology, 2023)
We report the case of a patient with common variable immunodeficiency (CVID) presenting with short stature and treated with recombinant human growth hormone (rhGH). Whole exome sequencing revealed a novel single-nucleotide duplication in the NFKB1 gene (c.904dup, p.Ser302fs), leading to a frameshift and thus causing NFKB1 haploinsufficiency. The variant was considered pathogenic and was later found in the patient’s mother, also affected by CVID. This is the first reported case of a patient with CVID due to NFKB1 mutation presenting with short stature. We analyzed the interconnection between NFKB1 and GH – IGF-1 pathways and we hypothesized a common ground for both CVID and short stature in our patient.